2000
DOI: 10.1093/humupd/6.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Extra-uterine pregnancy following assisted conception treatment

Abstract: Ectopic pregnancy may be the only life-threatening disease in which prevalence has increased as mortality has declined. The most prominent theory to explain this phenomenon involves increased sensitivity of serum beta-human chorionic gonadotrophin (HCG) immunoassay and improved quality of transvaginal ultrasound, combined with a heightened awareness and increased suspicion of the condition among clinicians which has allowed early detection of ectopic pregnancy. Laparotomy, once the standard treatment of ectopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 147 publications
0
18
0
Order By: Relevance
“…The risk factors for HP are endometriosis, periadnexal adhesion, tubal surgeries, and ART procedures that include a transfer near the uterine horn, excessive pressure in the syringe during transfer, and an excessive number of transferred embryos [1,3,4]. A HP should be considered in women who have had ART, whose chorionic gonadotropin level increases continuously after dilatation and curettage or spontaneous abortion, whose uterine fundus is larger than predicted for menstrual dates, who have more than one corpus luteum in a natural conception, or in whom vaginal bleeding is absent in the presence of signs and symptoms of ectopic gestation [5].…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for HP are endometriosis, periadnexal adhesion, tubal surgeries, and ART procedures that include a transfer near the uterine horn, excessive pressure in the syringe during transfer, and an excessive number of transferred embryos [1,3,4]. A HP should be considered in women who have had ART, whose chorionic gonadotropin level increases continuously after dilatation and curettage or spontaneous abortion, whose uterine fundus is larger than predicted for menstrual dates, who have more than one corpus luteum in a natural conception, or in whom vaginal bleeding is absent in the presence of signs and symptoms of ectopic gestation [5].…”
Section: Discussionmentioning
confidence: 99%
“…The estimated blood migration of transferred embryos towards the fallopian tube could explain the ovarian pregnancy after ET (1). The reverse migration could happen due to junctional zone contraction and strong endometrial waves in the fundal area of the uterus, which can be caused by the difficult ET, the manipulation with the tissue forceps, the high volume and pressure of the culture and the tilt-down position of the patient during ET (1,5). Some authors have reported fertilization of unrecovered oocytes if the coitus occurred near the day of the oocytes retrieval (1).…”
Section: Case Reportmentioning
confidence: 99%
“…Post conservative management of ectopic pregnancy adhesions develops in the pelvic area and in turn, presence of pelvic adhesions increase the rate of ectopic pregnancy [9,10].…”
Section: Introductionmentioning
confidence: 99%